Zirconia Sol
By controlling the particle size of zirconium oxide and increasing the distortion and deformation ratio of particles, an efficient zirconium oxide solution was prepared, which solved the problem of insufficient grinding rate and surface smoothness when grinding high-hardness materials in the prior art, and achieved more efficient grinding performance.
Patent Information
- Application Number
- JP2024573190
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-10-13
- Filing Date
- 2024-10-07
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2044-10-07
AI Technical Summary
When grinding high-hardness materials such as SiC, the existing zirconium oxide solutions are insufficient in grinding high-hardness materials, making it difficult to meet the needs of precision grinding.
By controlling the particle size of zirconium oxide between 5nm and 50nm, and through a specific preparation process, the distortion and deformation ratio of zirconium oxide particles is increased to 40% or more, thereby preparing a zirconium oxide solution with high grinding rate and low surface roughness.
When grinding high-hardness materials such as SiC, the grinding rate and surface smoothness are achieved, which is significantly better than the performance of traditional zirconium oxide solutions.
Smart Images

Figure 0007649432000002 
Figure 0007649432000003 
Figure 0007649432000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a zirconia sol. [Background technology]
[0002] Zirconia sol is used as a raw material powder for fine ceramics, precision abrasives, cosmetics, paint fillers, zirconia thin films, and the like (see, for example, Patent Documents 1 to 5). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-324639 A [Patent Document 2] International Publication No. 2012 / 169515 [Patent Document 3] WO 06 / 123562 [Patent Document 4] Japanese Patent Application Publication No. 2-137732 [Patent Document 5] Japanese Patent Application Publication No. 5-24844 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a zirconia sol which is more suitable as an abrasive grain for polishing. [Means for solving the problem]
[0005] The present invention provides the following: [1] Particle size D 50 is within the range of 5 nm or more and less than 50 nm, A zirconia sol having a ratio X of 40% or more obtained by the following procedure. <Procedure> Obtain a transmission electron microscope image containing 20 or more isolated particles. The following operations 1) to 5) are carried out for each isolated particle in the transmission electron microscope image. 1) Find the circumscribing circle and the inscribing circle that has the same center as the circumscribing circle. 2) Calculate the ratio of the diameter of the circumscribing circle to the diameter of the inscribing circle [(diameter of the circumscribing circle) / (diameter of the inscribing circle)]. 3) For all isolated particles in the transmission electron microscope image, the ratio [(circumscribed circle diameter) / (inscribed circle diameter)] is calculated. 4) Count the number of isolated particles A whose ratio [(circumscribed circle diameter) / (inscribed circle diameter)] is 2.0 or more. 5) The ratio X of the isolated particles A to all the isolated particles is calculated. (Proportion X(%)) = [(Number of isolated particles A) / (Total number of isolated particles)] × 100
[0006] Particles with the ratio [(circumscribed circle diameter) / (inscribed circle diameter)] of 2.0 or more are said to be angular, distorted particles. According to the configuration of [1], the proportion X is 40% or more, and a certain number or more of angular, distorted particles are included. Zirconia sols containing such particles are useful as polishing abrasives. In particular, according to the configuration of [1] above, the particle diameter D 50 In other words, according to the configuration of [4], the particle diameter D 50 The particle size is in the range of 5 nm to less than 50 nm, and a certain number of particles with angular or irregular shapes are included. 50 Zirconia sol containing irregularly shaped particles with a particle size of 5 nm or more and less than 50 nm is expected to provide higher rate and higher smoothness (low surface roughness) than existing products in precision polishing of semiconductors, etc. In particular, it is expected to provide higher rate and higher smoothness (low surface roughness) than existing products in polishing hard materials such as SiC. Effect of the Invention
[0007] According to the present invention, it is possible to provide a zirconia sol which is more suitable as an abrasive grain for polishing. [Brief description of the drawings]
[0008] [Figure 1] 1 is an X-ray diffraction chart of Example 2. [Diagram 2] FIG. 2 is a diagram for explaining the circumscribing circle and the inscribing circle of an isolated particle in a transmission electron microscope image. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to these embodiments. In this specification, zirconia (zirconium oxide) is a general term, and contains 10 mass % or less of impurity metal compounds including hafnia. In addition, in this specification, the expressions "contain" and "include" include the concepts of "contain", "include", "substantially consists of" and "consist only of".
[0010] [Zirconia sol] An example of the zirconia sol according to the present embodiment will be described below, however, the zirconia sol of the present invention is not limited to the following example.
[0011] The zirconia sol according to this embodiment is Particle size D 50 is within the range of 5 nm or more and less than 50 nm, The proportion X obtained by the following procedure is 40% or more. <Procedure> Obtain a transmission electron microscope image containing 20 or more isolated particles. The following operations 1) to 5) are carried out for each isolated particle in the transmission electron microscope image. 1) Find the circumscribing circle and the inscribing circle that has the same center as the circumscribing circle. 2) Calculate the ratio of the diameter of the circumscribing circle to the diameter of the inscribing circle [(diameter of the circumscribing circle) / (diameter of the inscribing circle)]. 3) For all isolated particles in the transmission electron microscope image, the ratio [(circumscribed circle diameter) / (inscribed circle diameter)] is calculated. 4) Count the number of isolated particles A whose ratio [(circumscribed circle diameter) / (inscribed circle diameter)] is 2.0 or more. 5) The ratio X of the isolated particles A to all the isolated particles is calculated. (Proportion X(%)) = [(Number of isolated particles A) / (Total number of isolated particles)] × 100
[0012] The particle diameter D 50 is preferably 45 nm or less, more preferably 40 nm or less. The particle diameter D 50 is preferably 7 nm or more, more preferably 9 nm or more. The particle diameter D 50 is preferably 7 nm or more and 45 nm or less, and more preferably 9 nm or more and 40 nm or less. The particle diameter D 50 The measurement method is more specifically the method described in the Examples.
[0013] The proportion X is preferably 50% or more, more preferably 55% or more, and further preferably 60% or more. The larger the ratio X, the more preferable it is, for example, 99% or less, 90% or less. The proportion X is preferably 50% or more and 99% or less, more preferably 55% or more and 90% or less, and further preferably 60% or more and 85% or less. More specifically, the ratio X is a value obtained by the method described in the Examples.
[0014] Particles with the ratio [(circumscribed circle diameter) / (inscribed circle diameter)] of 2.0 or more can be said to be angular, irregularly shaped particles. Zirconia sols containing such particles are useful as polishing abrasive grains. Particle size D 50 A zirconia sol containing irregularly shaped particles, in which the particle size is 5 nm or more and less than 50 nm and the proportion X is 40% or more, is expected to have a higher rate and higher smoothness (lower surface roughness) than existing products in precision polishing of semiconductors, etc. In particular, it is expected to have a higher rate and higher smoothness (lower surface roughness) than existing products in polishing hard materials such as SiC.
[0015] The zirconia sol is The crystallite size A on the monoclinic (-111) plane is 5.0 nm or more and 50.0 nm or less, The crystallite size B on the monoclinic (111) plane is 5.0 nm or more and 50.0 nm or less, The crystallite size ratio X represented by the following formula 1 is preferably 0.5 or more and 0.95 or less. <Expression 1> [Crystallite size ratio X] = [Crystallite size A on the monoclinic (-111) plane] / [Crystallite size B on the monoclinic (111) plane] Here, the crystallite size A and the crystallite size B are values calculated from powder X-ray diffraction measurement and analysis of the measurement.
[0016] When the crystallite size A is 5.0 nm or more and the crystallite size B is 5.0 nm or more, embedding in the polishing pad can be suppressed, and the polishing rate can be maintained high. In addition, when the crystallite diameter A is 50.0 nm or less and the crystallite diameter B is 50.0 nm or less, the penetration resistance to the polishing surface and the pad interface can be reduced. Since the penetration resistance can be reduced, the instantaneous pressure applied to the contact point can be reduced. As a result, the polishing rate can be maintained higher and the surface roughness can be reduced.
[0017] The crystallite size A is preferably 7.0 nm or more, and more preferably 9.0 nm or more. The crystallite size A is preferably 40.0 nm or less, and more preferably 35.0 nm or less. The crystallite size A is preferably 7.0 nm or more and 40.0 nm or less, and more preferably 9.0 nm or more and 35.0 nm or less.
[0018] The crystallite size B is preferably 7.0 nm or more, and more preferably 9.0 nm or more. The crystallite size B is preferably 40.0 nm or less, and more preferably 35.0 nm or less. The crystallite size B is preferably 7.0 nm or more and 40.0 nm or less, and more preferably 9.0 nm or more and 35.0 nm or less.
[0019] As described above, the crystallite diameter ratio X is preferably 0.5 or more and 0.95 or less. When the crystallite diameter ratio X is 0.95 or less, the polishing rate can be kept high. The present inventors speculate that the reason for this is as follows. When the crystallite diameter ratio X is 0.95 or less, the monoclinic crystal becomes a rectangular parallelepiped or rod-shaped crystal with a larger aspect ratio. Rectangular parallelepiped and rod-shaped crystals are less likely to rotate than spherical crystals (crystals with the crystallite diameter ratio X of 1). As a result, the frictional resistance with the polished surface increases, and the polishing rate is improved.
[0020] The crystallite size ratio X is preferably 0.55 or more, and more preferably 0.58 or more. The crystallite size ratio X is preferably 0.9 or less, and more preferably 0.87 or less. The crystallite size ratio X is preferably 0.55 or more and 0.9 or less, and more preferably 0.58 or more and 0.87 or less.
[0021] The zirconia sol preferably contains a tetragonal phase in a volume fraction of 2.0% to 90.0%. When the tetragonal phase is contained in a volume fraction of 2.0% to 90.0%, the surface roughness of the polished surface can be reduced while maintaining a high polishing rate. The present inventors speculate that the reason for this is as follows. The tetragonal phase has the property of undergoing a phase transition to the monoclinic phase when pressure is applied, and the phase transition to the monoclinic phase is accompanied by a volume expansion of several percent. Therefore, when zirconia sol is exposed to pressure at the interface between the pad and the polished surface, some of the tetragonal phase transitions to the monoclinic phase, and the volume expansion at that time breaks down the aggregation between the crystallites, breaking them apart. This relieves the exposed pressure. As a result, since this occurs intermittently during polishing, the instantaneous pressure applied to the polished surface by the polishing grains is suppressed, and the surface roughness can be reduced.
[0022] The content of the tetragonal phase is more preferably 5.0% or more, and further preferably 8.0% or more. The content of the tetragonal phase is more preferably 85.0% or less, and further preferably 80.0% or less. The content of the tetragonal phase is more preferably 5.0% or more and 85.0% or less, and further preferably 8.0% or more and 80.0% or less. The tetragonal crystals do not necessarily have to be contained, but the presence of the tetragonal crystals can reduce the surface roughness of the surface to be polished.
[0023] The zirconia sol preferably has a crystallite size ratio Y, represented by the following formula 2, of 0.3 or more and 1.2 or less. <Expression 2> [Crystallite size ratio Y] = [Crystallite size A on monoclinic (-111) plane] / [Crystallite size C on tetragonal (101) plane] Here, the crystallite size C is a value calculated from powder X-ray diffraction measurement and analysis of the measurement.
[0024] When the crystallite diameter ratio Y is 0.3 or more and 1.2 or less, the surface roughness of the polished surface can be further reduced. The present inventors speculate that the reason for this is as follows. When the crystallite size ratio Y is 0.3 or more and 1.2 or less, the phase transition is easily induced, that is, the instantaneous overpressure is more suppressed, and as a result, the surface roughness is smaller.
[0025] The crystallite size ratio Y is more preferably 0.4 or more, and further preferably 0.5 or more. The crystallite size ratio Y is more preferably 1.1 or less, and further preferably 1.0 or less. The crystallite size ratio Y is more preferably 0.4 or more and 1.1 or less, and further preferably 0.5 or more and 1.0 or less.
[0026] The concentration of the zirconia sol is not particularly limited, but is usually 1% by mass or more and 60% by mass or less in terms of ZrO2. When the concentration of the zirconia sol is 1% by mass or more, it is possible to prevent the zirconia concentration from decreasing when diluting with another solvent. When the concentration of the zirconia sol is 60% by mass or less, the viscosity of the sol is suppressed, and the stability is excellent. The concentration of the zirconia sol is more preferably 5% by mass or more, and further preferably 10% by mass or more. The concentration of the zirconia sol is more preferably 50% by mass or less, and further preferably 45% by mass or less. The concentration of the zirconia sol is more preferably from 5% by mass to 50% by mass, and further preferably from 10% by mass to 45% by mass.
[0027] The dispersion medium of the zirconia sol is not particularly limited, and examples thereof include hydrophilic organic solvents such as water, methanol, ethanol, 2-propanol, acetone, ether, etc., and mixtures of one or more of the hydrophilic organic solvents. The dispersion medium of the zirconia sol is preferably water (pure water or ion-exchanged water).
[0028] The pH of the dispersion medium of the zirconia sol is not particularly limited, but is preferably from 1 to 13, and more preferably from 2 to 12. When an acid such as nitric acid is contained, the pH is more preferably from 7 or less, or from 1 to 6. When the pH of the dispersion medium of the zirconia sol is 7 or less, the pH becomes far from the isoelectric point of zirconia, and the stability is improved.
[0029] In this specification, the zirconia sol does not contain additives such as potassium permanganate that impart a function as an abrasive. In other words, in this specification, a polishing dispersion refers to one containing zirconia sol and an additive for imparting a function as an abrasive, and a zirconia sol alone cannot be a polishing dispersion.
[0030] <Polishing performance> The zirconia sol preferably has a polishing rate of 0.5 μm / hour or more and a surface roughness Ra of 1.0 Å or less when polishing is performed using the polishing dispersion described below under the polishing conditions described below. When the polishing rate is 0.5 μm / hour or more and the surface roughness Ra of the surface to be polished is 1.0 Å or less, a polished surface with low surface roughness can be obtained in a short time.
[0031] 1. Preparation of polishing dispersion for polishing performance evaluation The zirconia sol is mixed with ion-exchanged water and potassium permanganate to prepare a polishing dispersion containing 15.0 mass % of zirconia and 1.2 mass % of potassium permanganate calculated as ZrO2. 2. Polishing conditions Substrate (polishing object): 4H-SiC wafer, 4 inches, Si surface, off 4 degrees, non-doped (surface roughness Ra: 1 Å) Polishing device: Single-sided polishing device (manufactured by ENGIS EJ-380N) Polishing pad: SUBA600 (Nitta DuPont) Polishing load: 280g / cm 2 Rotation speed of the platen: 80 rpm (linear speed: 9.5 m / min) Polishing time: 2 hours Supply rate of polishing composition: 10 mL / min Measurement area of polished object: 5.0μm×5.0μm (surface roughness measurement)
[0032] The polishing rate is more preferably 0.6 μm / hour or more, and further preferably 0.7 μm / hour or more. As long as the surface roughness does not exceed a certain level, the higher the polishing rate, the better. Specifically, the polishing rate is more preferably 5 μm / hour or less, and further preferably 3 μm / hour or less. The polishing rate is more preferably from 0.6 μm / hour to 5 μm / hour, and further preferably from 0.7 μm / hour to 3 μm / hour.
[0033] The surface roughness Ra of the surface to be polished is more preferably 0.9 Å or less, and further preferably 0.8 Å or less. The smaller the surface roughness Ra of the surface to be polished, the more preferable it is, for example, 0.1 Å or more, 0.2 Å or more. The surface roughness Ra of the surface to be polished is more preferably 0.1 Å or more and 0.9 Å or less, and further preferably 0.2 Å or more and 0.8 Å or less.
[0034] The zirconia sol according to this embodiment can be obtained, for example, by the following method for producing a zirconia sol.
[0035] [Method of manufacturing zirconia sol] An example of the method for producing the zirconia sol will be described below, however, the method for producing the zirconia sol is not limited to the following example.
[0036] The method for producing the zirconia sol according to this embodiment is as follows: Step A: Neutralizing the aqueous zirconium oxychloride solution by dropwise addition of aqueous ammonia Including, (1) The concentration of the aqueous zirconium oxychloride solution before carrying out the step A is 10% by mass or more, and the temperature is 60° C. or more and 95° C. or less; (2) The concentration of the ammonia water is 10% by mass or more, (3) the volume of the droplet of ammonia water dropped in the step A is 1.0 ml or less; (4) The dropwise addition of the ammonia water is carried out in two stages. In the first stage, the ammonia water is dropwise added in an amount of 0.9 moles or more and 1.1 moles or less per mole of Zr calculated as NH3, and then the mixture is maintained for 10 minutes or more and 120 minutes or less. (5) In the second stage, after the ammonia water is added dropwise, the mixture is kept for 10 minutes or more and 120 minutes or less, (6) During the dropwise addition of the ammonia water and during the holding period, the temperature of the aqueous zirconium oxychloride solution is maintained within a range of ±5° C. of the temperature at the start of the dropwise addition.
[0037] <Process A> First, in step A, aqueous ammonia is added dropwise to an aqueous zirconium oxychloride solution to neutralize it.
[0038] In this embodiment, ammonia water is used as a neutralizing agent for zirconium oxychloride. The concentration of the ammonia water is 10% by mass or more. The concentration of the ammonia water is preferably 15% by mass or more, and more preferably 20% by mass or more. The concentration of the ammonia water has no particular upper limit, but is, for example, 30% by mass or less, 28% by mass or less. The concentration of the ammonia water is preferably 15% by mass or more and 30% by mass or less, and more preferably 20% by mass or more and 28% by mass or less.
[0039] The concentration of the aqueous zirconium oxychloride solution before the step A is carried out is 10% by mass or more. The concentration of the aqueous zirconium oxychloride solution is preferably 15% by mass or more, and more preferably 18% by mass or more. The concentration of the aqueous zirconium oxychloride solution has no particular upper limit, but is, for example, 28% by mass or less, 25% by mass or less, and the like. The concentration of the aqueous zirconium oxychloride solution is preferably 15% by mass or more and 28% by mass or less, and more preferably 18% by mass or more and 25% by mass or less.
[0040] The temperature of the aqueous zirconium oxychloride solution before carrying out the step A is 60° C. or higher and 95° C. or lower.
[0041] The temperature of the aqueous zirconium oxychloride solution before carrying out the step A is preferably 65° C. or higher. The temperature of the aqueous zirconium oxychloride solution before carrying out the step A is preferably 90° C. or lower. The temperature of the aqueous zirconium oxychloride solution before carrying out the step A is preferably 65°C or higher and 90°C or lower.
[0042] The volume of the droplets of ammonia water dropped in the step A is 1.0 ml or less. The volume of the droplet is preferably 0.7 ml or less, more preferably 0.5 ml or less. The smaller the volume of the droplet, the more preferable, for example, 0.05 ml or more, 0.1 ml or more. The volume of the droplet is preferably 0.05 ml to 0.7 ml, more preferably 0.1 ml to 0.5 ml.
[0043] The dropwise addition of aqueous ammonia is carried out in two stages. In the first stage, the ammonia water is added dropwise in an amount of 0.9 moles or more and 1.1 moles or less per mole of Zr calculated as NH3, and then the mixture is maintained for 10 minutes or more and 120 minutes or less.
[0044] The time for dropping the ammonia water is not particularly limited, but for example, when 1000 ml of the ammonia water is dropped into 1000 ml of the zirconium oxychloride aqueous solution, the time is preferably 10 minutes or more and 120 minutes or less, more preferably 90 minutes or less, and further preferably 60 minutes or less.
[0045] The retention time (retention time in the first stage) is preferably 20 minutes or more, more preferably 30 minutes or more. The retention time is preferably 100 minutes or less, more preferably 90 minutes or less. The retention time is preferably from 20 minutes to 100 minutes, more preferably from 30 minutes to 90 minutes.
[0046] In the second stage, after the ammonia water is added dropwise, the mixture is maintained for 10 minutes or more and 240 minutes or less.
[0047] The amount of aqueous ammonia added dropwise in the second stage is not limited, but is 1 to 15 moles, preferably 2 to 10 moles, per mole of Zr calculated as NH3.
[0048] The time for dropping the aqueous ammonia in the second step is not particularly limited, but for example, when 1000 ml of the aqueous ammonia is dropped into 1000 ml of the aqueous zirconium oxychloride solution, the time is preferably 10 minutes or more and 120 minutes or less, more preferably 90 minutes or less, and further preferably 60 minutes or less.
[0049] The retention time (retention time after dropwise addition of aqueous ammonia in the second stage) is preferably 30 minutes or more, more preferably 60 minutes or more. The retention time is preferably 180 minutes or less, more preferably 150 minutes or less. The retention time is preferably 30 minutes or more and 180 minutes or less, and more preferably 60 minutes or more and 150 minutes or less.
[0050] During the dropwise addition of the aqueous ammonia and during the holding, the temperature of the aqueous zirconium oxychloride solution is maintained within a range of ±5° C. of the temperature at the start of the dropwise addition.
[0051] According to the method for producing the zirconia sol, by using the zirconium hydroxide obtained by controlling the above (1) to (6) as a raw material, a large number of particles having a distorted shape can be obtained, that is, a zirconia sol having the ratio X of 40% or more can be obtained.
[0052] After the step A, stirring is performed as necessary to homogenize the mixture. This results in a precipitate of zirconium hydroxide. The stirring time is not particularly limited, and is, for example, from 15 minutes to 120 minutes.
[0053] Thereafter, the zirconium hydroxide is washed as necessary. The washing is performed, for example, until the Cl concentration becomes a predetermined concentration or less. The predetermined concentration is preferably, for example, 0.01% or less. The washing method is not particularly limited, but for example, a method of repeatedly filtering out the zirconium hydroxide and dispersing it in ion-exchanged water can be mentioned.
[0054] <Process B> After the step A, the zirconium hydroxide obtained in the step A is heated and aged under acidic conditions. To make the zirconium hydroxide acidic, an acid is usually added as a peptizing agent. If necessary, water may be added to adjust the concentration. The concentration is not particularly limited, but is preferably 1% by mass or more and 30% by mass or less, and more preferably 5% by mass or more and 20% by mass or less, calculated as ZrO2.
[0055] The deflocculating agent for zirconium hydroxide is not particularly limited so long as it is a water-soluble inorganic or organic acid, and examples thereof include hydrochloric acid, nitric acid, sulfuric acid, acetic acid, lactic acid, citric acid, tartaric acid, malic acid, mandelic acid, and the like. Hydrochloric acid and nitric acid are preferred because, even if they are present in excess in the zirconia sol, they can be easily removed by purification with water after the zirconia sol is produced. The amount of the deflocculating agent to be added is preferably acid / ZrO2 (molar ratio)=0.01 or more and 3 or less, more preferably 0.1 or more and 1.5 or less. When the acid / ZrO2 (molar ratio) is 0.01 or more, the zirconium hydroxide can be sufficiently peptized. Also, since there is little quantitative effect even if the acid / ZrO2 (molar ratio) exceeds 3, it is economical to set the acid / ZrO2 (molar ratio) to 3 or less.
[0056] Next, in order to peptize the zirconium hydroxide and simultaneously convert it into zirconium oxide, heating and aging are performed. From the viewpoint of yield, the heating and aging temperature is preferably 70°C or higher, more preferably 80°C or higher. The heating temperature is preferably 200°C or lower, more preferably 180°C or lower. The heating temperature is preferably 70°C or higher and 200°C or lower, more preferably 80°C or higher and 180°C or lower. When the aging temperature is 70° C. or higher, the deflocculation reaction proceeds smoothly, and when the aging temperature is 200° C. or lower, the aggregation is not too strong and the dispersibility is good. From the viewpoint of yield, the heating and aging time is preferably 24 hours or more, more preferably 48 hours or more. The heating and aging time is preferably 120 hours or less, more preferably 100 hours or less. The heating and aging time is preferably 24 hours or more and 120 hours or less, more preferably 48 hours or more and 100 hours or less.
[0057] Thereafter, after cooling to room temperature, ultrafiltration may be carried out to concentrate the zirconia sol. Excess acid can be easily removed using ultrafiltration. According to the method for producing zirconia sol according to the present embodiment, first, ammonia water is used as a neutralizing agent. Since ammonia water is used as a neutralizing agent, a zirconia sol having a ratio X of 40% or more can be obtained. Although the reason is unclear, the inventors speculate that since ammonia water is a weak alkali compared to a strong alkali such as a sodium hydroxide aqueous solution, the generation of nuclei that become particles is slow, resulting in a distorted shape compared to when a strong alkali is used. Although the reason for this is unclear, the process by which an aqueous solution of zirconium oxychloride reacts with aqueous ammonia to produce zirconium hydroxide is thought to be as follows (1) and (2). (1) The reaction of zirconium oxychloride with ammonia produces a zirconium hydroxide nucleus (presumably a cluster with the chemical formula {Zr(OH)4}n), (2) The aggregation of zirconium hydroxide nuclei and the grain growth of the zirconium hydroxide nuclei proceed simultaneously. In this regard, the inventors presume that the concentration of the initial zirconium oxychloride aqueous solution, the concentration of ammonia water, and the volume of the droplets when the ammonia water is added dropwise are determining factors for the nucleation rate and the density of the nuclei, and as a result, they become factors for controlling the balance between the aggregation of the nuclei and the grain growth of the nuclei in the above (2).The particle characteristics (particle size, shape, etc.) of the finally obtained zirconia sol are considered to be determined by the particle characteristics (particle size, shape, etc.) of the zirconium hydroxide produced in step A.
[0058] The method for producing the zirconia sol according to this embodiment has been described above. EXAMPLES
[0059] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention. Note that the zirconia sol in the examples and comparative examples contains 1 to 3 mass % of hafnium as an inevitable impurity relative to zirconium (calculated by the following formula (X)). <Expression(X)> ([Mass of hafnium oxide] / ([Mass of zirconium oxide]+[Mass of hafnium oxide]))×100(%)
[0060] The maximum and minimum values of the content of each component shown in the following examples should be considered as the preferred minimum and maximum values of the present invention, regardless of the contents of other components. Furthermore, the maximum and minimum values of the measured values shown in the following examples should be considered as the preferred minimum and maximum values of the present invention, regardless of the content (composition) of each component.
[0061] [Preparation of zirconia sol]
[0062] Example 1 In the first step, 138 g of ammonia water (10% by mass) adjusted to 25°C was added dropwise over 10 minutes to 1000 g of an aqueous zirconium oxychloride solution (10% by mass in terms of ZrO2) adjusted to 75°C using a mantle heater. At this time, the number of liquid delivery tubes and the drop rate were adjusted so that the volume of the droplets of ammonia water was in the range of 0.1 to 0.5 ml. Stirring was then continued for 90 minutes. Then, in the second step, 1242 g of ammonia water (10% by mass) adjusted to 25°C was added dropwise over 30 minutes. In the second step, the number of liquid delivery tubes and the drop rate were also adjusted so that the volume of the droplets of ammonia water was in the range of 0.1 to 0.5 ml. Stirring was then continued for 10 minutes to obtain a precipitate of zirconium hydroxide. The aqueous zirconium oxychloride solution was adjusted to maintain the initial temperature within ±5°C during the drop of ammonia water and during stirring after the drop. The zirconium hydroxide was filtered off and the washing procedure of dispersing it again in ion-exchanged water was repeated until the Cl concentration became 0.01% or less. The concentration of the zirconium hydroxide after washing was 22.9 mass% in terms of ZrO2. 437 g of the obtained zirconium hydroxide was mixed with 535 g of ion-exchanged water and 28.0 g of nitric acid (60 mass%) to prepare a slurry, which was placed in a separable flask and stirred under reflux at 100°C for 120 hours. The obtained zirconia sol precursor was purified using ultrafiltration to obtain the zirconia sol according to Example 1. The ZrO2 concentration of the sol was 20 mass%, the pH was 3.1, and the particle diameter D 50 was 44 nm. Example 2 In the first step, 138 g of ammonia water (10% by mass) adjusted to 25°C was added dropwise over 10 minutes to 1000 g of an aqueous zirconium oxychloride solution (10% by mass in terms of ZrO2) adjusted to 75°C using a mantle heater. At this time, the number of liquid delivery tubes and the drop rate were adjusted so that the volume of the droplets of ammonia water was in the range of 0.1 to 0.5 ml. Stirring was then continued for 60 minutes. Then, in the second step, 1242 g of ammonia water (10% by mass) adjusted to 25°C was added dropwise over 30 minutes. In the second step, the number of liquid delivery tubes and the drop rate were also adjusted so that the volume of the droplets of ammonia water was in the range of 0.1 to 0.5 ml. Stirring was then continued for 30 minutes to obtain a precipitate of zirconium hydroxide. The aqueous zirconium oxychloride solution was adjusted to maintain the initial temperature within ±5°C during the drop of ammonia water and during the stirring after the drop. The zirconium hydroxide was filtered off and the washing procedure of dispersing it again in ion-exchanged water was repeated until the Cl concentration became 0.01% or less. The concentration of the zirconium hydroxide after washing was 23.8% by mass in terms of ZrO2. A zirconia sol was obtained in the same manner as in Example 1, except that 420 g of the obtained zirconium hydroxide was mixed with 535 g of ion-exchanged water and 28.0 g of nitric acid (60% by mass). The ZrO2 concentration of the sol was 20% by mass, the pH was 3.3, and the particle diameter D 50 was 43 nm.
[0063] Example 3 In the second step, 1242 g of aqueous ammonia (10% by mass) adjusted to 25° C. was added dropwise over 30 minutes, and the stirring was continued for 60 minutes, to obtain zirconium hydroxide in the same manner as in Example 1. The concentration of the zirconium hydroxide after washing was 23.2 mass% in terms of ZrO2. A zirconia sol was obtained in the same manner as in Example 2, except that 431 g of the obtained zirconium hydroxide was mixed with 541 g of ion-exchanged water and 28.0 g of nitric acid (60 mass%). The ZrO2 concentration of the sol was 20 mass%, the pH was 3.2, and the particle diameter D 50 was 39 nm.
[0064] Example 4 In the second step, 1242 g of aqueous ammonia (10% by mass) adjusted to 25° C. was added dropwise over 30 minutes, and the stirring was continued for 120 minutes, to obtain zirconium hydroxide in the same manner as in Example 1. The concentration of the zirconium hydroxide after washing was 22.6% by mass in terms of ZrO2. A zirconia sol was obtained in the same manner as in Example 2, except that 442 g of the obtained zirconium hydroxide was mixed with 530 g of ion-exchanged water and 28.0 g of nitric acid (60% by mass). The ZrO2 concentration of the sol was 20% by mass, the pH was 3.3, and the particle diameter D 50 was 34 nm.
[0065] Comparative Example 1 1380 g of ammonia water (10% by mass) adjusted to 25°C was added dropwise over 40 minutes to 1000 g of an aqueous solution of zirconium oxychloride (10% by mass calculated as ZrO2) adjusted to 25°C. At this time, the number of liquid delivery tubes and the dropping speed were adjusted so that the volume of the droplets of ammonia water was in the range of 0.1 to 0.5 ml. Thereafter, stirring was continued for 10 minutes to obtain a precipitate of zirconium hydroxide. The zirconium hydroxide was filtered off and dispersed again in ion-exchanged water, and a washing operation was repeated. The above operation was performed until the Cl concentration became 0.01% or less. The concentration of the zirconium hydroxide after washing was 28.4 mass% in terms of ZrO2. A zirconia sol was obtained in the same manner as in Example 1, except that 352 g of the obtained zirconium hydroxide was mixed with 620 g of ion-exchanged water and 28.0 g of nitric acid (60 mass%). The ZrO2 concentration of the sol was 20 mass%, the pH was 3.3, and the particle diameter D 50 was 72 nm.
[0066] [Particle size D 50 Measurement of The zirconia sol of each of the examples and comparative examples was diluted with ion-exchanged water to 1.0 mass% in terms of ZrO2, and then placed in an apparatus (a dynamic light scattering particle size distribution measuring apparatus ("Zetasizer Nano ZS" manufactured by Malvern Panalytical)) to measure the particle diameter D of the zirconia sol. 50 (Volume frequency distribution standard) was measured. The results are shown in Table 1. <Measurement conditions> Measurement temperature: 25℃ Scattering angle: 173° Dispersoid: ZrO2 Dispersion medium: water Cell: Genuine disposable cell Repeat count: 3 (particle diameter D 50 is the average of three times)
[0067] [Powder X-ray diffraction measurement and analysis] The zirconia sols obtained in the examples and comparative examples were dried at 100°C and measured with an X-ray diffractometer ("RINT2500" manufactured by Rigaku) to obtain X-ray diffraction charts. The measurement conditions were as follows. The X-ray diffraction chart of Example 2 is shown in Figure 1. <Measurement conditions> Measurement equipment: X-ray diffraction equipment (Rigaku, RINT2500) Source: CuKα source Tube voltage: 50kV Tube current: 300mA Scanning angle: 2θ=10~50° Scanning speed: 1° / min
[0068] The chart was analyzed in the range of 2θ=20-40° using Powder XRD, SmartLab Studio II (RIGAKU), and the crystallite size and tetragonal ratio for each crystal plane were calculated. The results are shown in Table 1. Table 1 also shows the crystallite size ratio X ([crystallite size A on monoclinic (-111) plane] / [crystallite size B on monoclinic (111) plane]) and the crystallite size ratio Y ([crystallite size A on monoclinic (-111) plane] / [crystallite size C on tetragonal (101) plane]). This calculation was carried out on three peaks whose peak tops are located in the ranges of 27.5 to 28.5°, 29.5 to 30.5°, and 31.0 to 32.0° of the diffraction chart. 27.5 to 28.5° is attributed to m(-111), 29.5 to 30.5° is attributed to t(101) or c(111), and 31.0 to 32.0° is attributed to m(111). Even if the peak angle falls outside the above range or the peak is split due to a change in the lattice constant caused by the solid solution of other elements in zirconia, it was decided to provide it for this analysis as long as it is appropriate to attribute it to the above crystal plane. In this specification, t(101) and c(111) do not necessarily need to be distinguished from each other, and are treated as the same. The analysis was carried out under the following procedures and conditions. After loading the powder X-ray diffraction measurement data into the Powder XRD software in SmartLab Studio II, peak processing is performed. The peak profiling conditions are set as follows: Peak search: Check box ON Pre-processing:Customized Method: Second order differential method σ cut value: 3 (if no clearly visible peak is detected, adjust between 0.5 and 3) Profile fitting: Check box ON Peak shape: Split pseudo-Voigt function Background Type: B-Spline Fitting conditions: Automatic Refine background: Check box ON To calculate the crystallite size and crystallite size ratio, use the values shown in the Crystallite Size (Å) column displayed in the Peak List tab (ignore the values in parentheses). To calculate the tetragonal crystal ratio, the value displayed in the column of integrated intensity (count°) displayed in the Peak List tab (values in parentheses are ignored) is used.
[0069] The tetragonal phase ratio was calculated from the following formula based on the diffraction peak intensity I of each crystal plane obtained by the above analysis. [Tetragonal phase ratio (%)]={It(101)+Ic(111)} / {It(101)+Ic(111)+Im(-111)+Im(111)}×100 Here, Im(-111) is the diffraction intensity of (-111) in the monoclinic phase, and Im(111) is the diffraction intensity of (111) in the monoclinic phase. It(101) is the diffraction intensity of (101) in the tetragonal phase. Ic(111) is the diffraction intensity of (111) in the cubic phase.
[0070] [Measurement of particle shape] First, TEM images (transmission electron microscope images) of the zirconia sols of the examples and comparative examples were obtained. The TEM images were taken using a transmission electron microscope (Hitachi, Ltd., product name: HV-8100) with a field of view of 1.15 μm×0.90 μm. Next, the number of isolated particles was visually counted. Specifically, the diameter of the circumscribed circle circumscribing the particle was determined to be the particle diameter D of the zirconia sol. 50 The number of particles that are 70% or more of the diameter of the circumscribing circle was counted. When there are multiple circumscribing circles that circumscribe a particle, the one with the smallest ratio (see "2") between the diameter of the circumscribing circle and the diameter of the inscribing circle (concentric inscribing circle) that has the same center as the circumscribing circle was used. Note that the diameter of the circumscribing circle that circumscribes a particle is the particle diameter D of the zirconia sol. 50 Particles less than 70% of the particle size were not counted because they have low abrasive effectiveness. When the number of isolated particles was 20 or more, the TEM image was used as the image to be evaluated. When the number of isolated particles was less than 20, a TEM image of a different field of view was taken, and this was repeated until a TEM image with 20 or more isolated particles was obtained. The following procedure was carried out for each isolated particle in the obtained TEM image (the isolated particle to be counted). 1) First, the circumscribing circle of the particle and the inscribing circle with the same center (concentric inscribing circle) were obtained (see Figure 2). The definitions of the circumscribing circle and inscribing circle are the same as those in the MCC method of circularity in JIS B 7451:1997. 2) Next, the ratio of the diameter of the obtained circumscribing circle to the diameter of the inscribing circle [(diameter of the circumscribing circle) / (diameter of the inscribing circle)] was calculated. 3) The ratio [(circumscribed circle diameter) / (inscribed circle diameter)] was calculated for all isolated particles in the TEM image (all isolated particles that were counted). 4) The number of isolated particles (hereinafter also referred to as "isolated particles A") having a ratio [(circumscribed circle diameter) / (inscribed circle diameter)] of 2.0 or more was counted. 5) The proportion of isolated particles A to all isolated particles (all isolated particles counted) (hereinafter also referred to as "proportion X") was determined. (Proportion X(%)) = [(Number of isolated particles A) / (Total number of isolated particles)] × 100 The results are shown in Table 1. Note that FIG. 2 shows an example of how to determine the circumscribing circle of a particle and the inscribing circle (concentric inscribing circle) that has the same center as the circumscribing circle, and is not a TEM image of the embodiment.
[0071] [Polishing performance evaluation] The zirconia sol of the examples and comparative examples was mixed with ion-exchanged water and potassium permanganate to prepare a polishing dispersion of 15 mass% in terms of ZrO2 and 1.2 mass% in terms of KMO4. Using this polishing dispersion, a SiC wafer was polished, and the polishing speed and the surface roughness Ra of the polished surface were measured. The polishing conditions were as follows: Substrate (polishing object): 4H-SiC wafer, 4 inches, Si surface, off 4 degrees, non-doped (surface roughness Ra: 1 Å) Polishing device: Single-sided polishing device (manufactured by ENGIS EJ-380N) Polishing pad: SUBA600 (Nitta DuPont) Polishing load: 280g / cm 2 Rotation speed of the platen: 80 rpm (linear speed: 9.5 m / min) Polishing time: 2 hours Supply rate of polishing composition: 10 mL / min Measurement area of polished object: 5.0μm×5.0μm (surface roughness measurement)
[0072] The removal rate was determined by measuring the weight of the substrate before and after polishing and calculating the difference therebetween. The surface roughness (arithmetic mean roughness (Ra)) of the polished surface of the object to be polished was measured using a Bruker AFM "Dimension Edge" under the condition of a viewing angle of 5.0 μm x 5.0 μm. The results are shown in Table 1.
[0073] [Table 1]
Claims
[Claim 1] Particle diameter D 50 is in the range of 5 nm or more and less than 50 nm, A zirconia sol obtained by the following procedure, characterized in that the ratio X is 40% or more. <Procedure> A transmission electron microscope image is obtained that contains 20 or more isolated particles. The following operations 1) to 5) are carried out for each isolated particle in the transmission electron microscope image. 1) Find the circumscribing circle and the inscribing circle that has the same center as the circumscribing circle. 2) The ratio of the diameter of the obtained circumscribing circle to the diameter of the inscribing circle [(diameter of the circumscribing circle) / (diameter of the inscribing circle)] is calculated. 3) For all isolated particles in the transmission electron microscope image, the ratio [(circumscribed circle diameter) / (inscribed circle diameter)] is calculated. 4) The number of isolated particles A having a ratio [(circumscribed circle diameter) / (inscribed circle diameter)] of 2.0 or more is counted. 5) The ratio X of the isolated particles A to all the isolated particles is calculated. (Proportion X (%)) = [(Number of isolated particles A) / (Total number of isolated particles)] × 100
Citation Information
Patent Citations
Zirconium oxide particle and method for producing the same
JP2005170700A
Method for manufacturing tetragonal zirconia sol
JP2005330174A
Zirconia fine particle and method for producing the same
JP2010105892A
Polishing slurry containing zirconia particles and method for using the polishing slurry
JP2014504324A
SOL HAVING AMORPHOUS Zr-O-BASED PARTICLE AS DISPERSOID, AND METHOD FOR PRODUCING THE SAME
JP2016069213A